2014
DOI: 10.1080/00036846.2013.866207
|View full text |Cite
|
Sign up to set email alerts
|

Financial market development and trade openness: evidence from emerging economies

Abstract: International trade is said to be the engine of economic growth. Despite an enormous effort to explain this phenomenon, the relationship between financial market development and trade openness and integration into the world economy is still an enigma. This article investigates the relationship between financial market development and trade openness. To do this, we develop a long-run and short-run model (a bounds testing approach to cointegration) for 18 emerging economies over the period 1980 to 2011. Estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
(53 reference statements)
4
27
0
Order By: Relevance
“…David et al (2014) investigated the interaction between development of financial sector and openness in 34 African countries employing panel regression and did not find a robust relationship among financial sector development and financial and trade openness. On the other side, Niroomand et al (2014) analyzed the interaction between development of financial sector and trade openness in 18 emerging markets during 1980-2011period employing ARDL approach and revealed that financial development had positive impact on trade openness in short and long run. Zhang et al (2015) also researched the interplay between financial sector development and openness in China during 2000-2009 period employing dynamic panel regression and revealed that openness affected the efficiency and competition of financial sector positively, but affected the size of financial sector negatively.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…David et al (2014) investigated the interaction between development of financial sector and openness in 34 African countries employing panel regression and did not find a robust relationship among financial sector development and financial and trade openness. On the other side, Niroomand et al (2014) analyzed the interaction between development of financial sector and trade openness in 18 emerging markets during 1980-2011period employing ARDL approach and revealed that financial development had positive impact on trade openness in short and long run. Zhang et al (2015) also researched the interplay between financial sector development and openness in China during 2000-2009 period employing dynamic panel regression and revealed that openness affected the efficiency and competition of financial sector positively, but affected the size of financial sector negatively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Theoretical considerations on finance-growth nexus dated back to Bagehot (1873) and extensive theoretical and empirical studies have researched the financegrowth nexus until today especially since emergence of theories of endogenous growth (see Nyankomo and Stephen (2015)). Theoretical studies suggest that development of financial sector contributes to the growth positively by way of several channels as follows (Valderrama, 2003):…”
Section: Introductionmentioning
confidence: 99%
“…In terms of trade openness, the results show that a percentage increase in trade openness promotes stock market development by approximately 2.513 per cent. This positive influence of trade openness on financial market development, including stock market development, is well documented in the literature (see Newbery & Stiglitz, 1984;Rajan & Zingales, 2003;Law & Habibullah, 2009;Niroomand et al, 2014;Ho, forthcoming openness and financial development is that, in the short run, an increase in trade openness leads to higher exposure to foreign competition and technology, as well as the changes in factor prices and product prices. Such changes will increase uncertainty and reduce investment, thereby inhibiting stock market growth in the short run.…”
Section: Empirical Analysis Using Ardl Bounds Testing Proceduresmentioning
confidence: 64%
“…The study uses the sum of exports and imports of goods and services as a share of GDP to measure trade openness. Studies using this proxy to measure trade openness include the studies by Rajan and Zingales (2003), El-Wassal (2005), and Niroomand et al (2014).…”
Section: Trade Openness (Open)mentioning
confidence: 99%
“…Trade openness (TO) in this study is proxied by the sum of exports and imports of goods and services as a ratio of GDP. The more open the economy the more developed the stock market (see Law and Habibullah, 2009;Niroomand et al, 2014). The coefficient is expected to be positive.…”
Section: Data Description and Sourcementioning
confidence: 99%